Examining the Role of Compensation and Work Ethic in Enhancing Teacher Performance - Ari Kartiko; Cut Ulfatul Ulya Manik (Academicus: Journal of Teaching and Learning, 2026)
Teachers play a pivotal role in educational implementation, functioning not only as administrative executors but also as strategic agents in enhancing educational quality through professional competence and moral integrity. In Islamic educational institutions, teacher performance is particularly crucial, as it reflects the integration of pedagogical expertise and ethical values. However, prior studies generally examine compensation and work ethic separately or focus mainly on public schools, creating a gap in understanding their combined effect within Islamic secondary education. This study investigates the influence of compensation and work ethic on teacher performance at MAN 2 Mojokerto. Using a quantitative approach, data were collected from all 62 teachers through a census-based survey. Instrument validity and reliability were confirmed, and multiple linear regression analysis was conducted using IBM SPSS version 22. The findings reveal that compensation and work ethic simultaneously exert a positive and significant effect on teacher performance (F = 71.561 > F-table = 3.15). Partially, compensation shows a more dominant influence (β = 0.736) than work ethic (β = 0.214). These results provide empirical evidence of the relative contribution of financial and ethical factors in shaping teacher performance within Islamic educational settings. The study underscores the importance of implementing equitable, performance-based compensation systems alongside strengthening work ethic to achieve sustainable improvements in educational quality.